Delineation of EFTUD2 Haploinsufficiency‐Related Phenotypes Through a Series of 36 Patients. Issue 4 (5th March 2014) - Lehalle, Daphné; Gordon, Christopher T.; Oufadem, Myriam; Goudefroye, Géraldine; Boutaud, Lucile; Alessandri, Jean‐Luc; Baena, Neus; Baujat, Geneviève; Baumann, Clarisse; Boute‐Benejean, Odile; Caumes, Roseline; Decaestecker, Charles; et al.
<x xml:space="preserve">Abstract</x> We have delineated the clinical spectrum of Mandibulofacial dysostosis, Guion‐Almeida type (MFDGA) in a series of 36 patients with mutations in EFTUD2, which encodes a component of the spliceosome. Despite high phenotypic variability amongst MFDGA patients, a characteristic facial gestalt provides the most useful diagnostic handle. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>